STRATEGI-STRATEGI GURU DI INDONESIA DALAM MENGIDENTIFIKASI ANAK BERKELUARBIASAAN GANDA (TWE) - Maliha, Siti (Universitas Borneo Tarakan, 2023)
AbstractThere are many children who have talents and perform well in some areas but also have learning difficulties or behaviour problems. Their disabilities combined with their high abilities produce a unique population of students who may fail to demonstrate either high academic performance or specific disabilities. Identifying and recognizing these â€œtwice-exceptional (TWE)â€ children in the classroom can be challenging for teachers. Thus, it is important for teachers to be able to recognize and understand the characteristics of these children to provide appropriate educational assistance to help them achieve their potential. This research program aimed to determine the strategies teachers used to identify twice-exceptional children in their classrooms in Indonesia by using an online TWE questionnaire and focus group discussions. The questionnaire data has been interpreted through descriptive statistics and thematic analysis guided the interpretation of the focus group discussion data. The result obtained indicated that knowledge of most teachers about TWE children was between slightly and moderately familiar. They are actually quite often working with gifted students with learning difficulties and some with gifted children with emotional difficulties. However, they did not realize that this term of TWE children existed in their schools. They also need to improve their skills for engaging with TWE children in a classroom in terms of identification and teaching strategies.Â Keywords: TWE (twice-exceptional) children, Teaching strategies, Identification, Familiarities, Teachers